The tax prescription of Administration’s actions to require payment, determine the tax obligation and apply sanctions. Critical review and brief reflections - Aguayo López, Juan Maximiliano (2021)
This article makes a general review of some of the main aspects related to the tax prescription of the actions of the Tax Administration referred to demanding payment, determining the tax obligation and applying sanctions. For this purpose, the Peruvian legal regime contained in the Tax Code, and the applicable jurisprudence, are critically analyzed in order to identify those areas that deserve more attention from academia, the tax dispute resolution entities and the legislator.